Resorcinol-formalin method. Complexity of retreatment and solutions. A clinical case (Эндодонтия Today)
Presented clinical case is to show how to solve problems arising in the retreatment of «resorcined» teeth. Teeth treated with resorcinol-formalin method have a high enough percentage of complications in the long-term periods. In the absence of conditions for re-treatment of the root canal of a tooth its extraction is recommended. Difficulties arise when endo-revision of «resorcined» teeth in most cases can be solved only by using special tools and techniques: cone computed tomography and qualitative increase (dental microscope), an ultrasonic device, abundant irrigation and high-quality three-dimensional obturation of the root canal system.